PERENCANAAN JEMBATAN RANGKA BAJA BENTANG 50 METER - Risky Amaliya Putri, Sudarmanto, Yunaefi (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2015)
To facilitate the flow of transport from one region to the other region dan increase sectors of the economy the need for bridges as a means of connecting. Steel bridge is the one arranged from steel beam joined with gusset plate, binder keeling nails, bolts or welding. The purpose of the study is to design a 50 m-spam steel truss bridge of 10,4 m width. The design was based on Highway Bridge Loading Design, ASD and PPBBI 1984. The concrete strength is of (fc ') 30 MPa and the steel strength of BJ 44. Designed manually with no pillar, the bottom only consists of abutment and foundation. The main framework was designed by employing equilibrium of gusset point dan reitter method was employed to found out the beam force and influential linesof the framework. The soil survey data were obtained throught Begemann Friction Cone (Bikonus) or Dutch Cone Mechanical type test. The soil is melatirely similar type of sandy clay mix and hard soil in the depth of 5 meters. The design result in the main framework using profile WF 400 x 400 x 20 x 35, longitudinal girder of WF 350 x 350 x 13 x 13 dan crossed girder of WF 800 x 300 x 16 x 30 The foundation is of pile foundation at IDR 5.543.070.300,00,- within 172 work days.Keywords: steel, truss, bridge